Oxidative damage and carcinogenesis - Strzelczyk, Joanna Katarzyna; Wiczkowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2012)
Oxygen is an essential element to conduct life processes but some of the metabolic byproducts e.g. reactive oxygen species (ROS), are toxic for living organisms. Endogenous ROS are produced e.g. reduction of dioxygen; some exogenous sources of radicals also exist, including nicotine and ionizing radiation. Reactive oxygen species include superoxide anion, hydroxyl radical, singlet oxygen, hydrogen peroxide and hypochlorous acid. Carcinogenesis is a multistep process. The exact reasons for the development of cancer are still unknown. Many factors contribute to the development of carcinogenesis, one of which is oxidative stress. Oxidative stress is defined as an imbalance between oxidizing agents (pro-oxidants) and antioxidants, agents that protect biomolecules against injury by pro-oxidants. When reactive oxygen species are overproduced it can damage nucleic acids, proteins and lipids. ROS are considered as a significant class of carcinogens participating in cancer initiation, promotion and progression.